Accurate, practical and cost-effective assessment of carotid stenosis in the UK. - Wardlaw, J; Chappell, F; Stevenson, M; De Nigris, E; Thomas, S; Gillard, J; Berry, E; Young, G; Rothwell, P; Roditi, G; Gough, M; Brennan, A; et al. (2006)
OBJECTIVES: To determine whether less invasive imaging tests [ultrasound (US), magnetic resonance angiography (MRA), computed tomographic angiography (CTA) and contrast-enhanced MRA (CEMRA)], alone or combined, could replace intra-arterial angiography (IAA), what effect this would have on strokes and deaths, endarterectomies performed and costs, and whether less invasive tests were cost-effective. DATA SOURCES: Electronic databases covering the years 1980-2003 inclusive, updated to April 2004. Key journals from 1990 to the end of 2002. REVIEW METHODS: The authors constituted a panel of experts in stroke, imaging, vascular surgery, statistics and health economic modelling. The accuracy of less invasive carotid imaging was systematically reviewed using Standards for Reporting of Diagnostic Accuracy (STARD) methodology, supplemented by individual patient data from UK primary research and audit studies. A systematic review of the costs of less invasive tests, outpatient clinics, endarterectomy and stroke was performed, along with a microcosting exercise. A model of the process of care following a transient ischaemic attack (TIA)/minor stroke was developed, populated with data from stroke epidemiology studies in the UK, effects of medical and surgical interventions, outcomes, quality of life and costs. A survey of UK stroke prevention clinics provided typical timings. Twenty-two different carotid imaging strategies were evaluated for short- and long-term outcomes, quality-adjusted life-years (QALYs) and net benefit. RESULTS: In 41 included studies (2404 patients, median age 60-65 years), most data were available on 70-99% stenosis. CEMRA was the most accurate [sensitivity 0.94, 95% confidence interval (CI) 0.88 to 0.97; specificity 0.93, 95% CI 0.89 to 0.96], compared with US, MRA and CTA, which were all similar (e.g. for US: sensitivity 0.89, 95% CI 0.85 to 0.92; specificity 0.84, 95% CI 0.77 to 0.89). Data for 50-69% stenoses and on combinations of tests were too sparse to be reliable. There was heterogeneity between studies for all imaging modalities except for CTA. The individual patient data (2416 patients) showed that the literature overestimated test accuracy in routine practice and that, in general, tests perform with higher sensitivity and specificity in asymptomatic than in symptomatic arteries. In the cost-effectiveness model, on current UK timings, strategies allowed more patients to reach endarterectomy very quickly, and where those with 50-69% stenosis would be offered surgery in addition to those with 70-99%, prevented most strokes and produced greatest net benefit. This included most strategies with US as first or repeat test, and not those with IAA. However, the model was sensitive to less invasive test accuracy, cost and timing of endarterectomy. In patients investigated late after TIA, test accuracy is crucial and CEMRA should be used before surgery. CONCLUSIONS: In the UK, less invasive tests can be used in place of IAA if radiologists trained in carotid imaging are available. Imaging should be carefully audited. Stroke prevention clinics should reduce waiting times at all stages to improve speed of access to endarterectomy. In patients presenting late after TIA, test accuracy is very important and US results should be confirmed by CEMRA, as patients with 50-69% stenosis are less likely to benefit. More data are required to define the accuracy of the less invasive tests, with improvements made in the data collection methods used and how data are presented. Consideration should also be given to the use of new technologies and randomised trials.